Mushroom Cultivation Business Development Strategy with BMC Model During Pandemic Covid 19 - Retno Endah Supeni; Bayu Wijayantini (Universitas Muhammadiyah Jakarta, 2023)
The COVID-19 pandemic has greatly affected various aspects of people's lives. However, despite all the adversity, several businesses are still able to survive and are expected to continue growing during the crisis. Village-Owned Enterprises (BUMDes) are considered important elements that can play a significant role in awakening and stimulating a sluggish economy in the midst of a pandemic. BUMDes and the mushroom cultivation business unit face several obstacles in marketing, human resources, and increasingly high competition. The type of research used is descriptive with a qualitative approach. This study aims to determine the business development strategy used by the BUMDes Pontang Mushroom Cultivation Business to achieve a new model for business development by using the design of the nine elements of the Business Model Canvas (BMC), which include customer segment, value proposition, channel, customer relationship, revenue stream, key resources, key activities, key partnerships, and cost structure. The results of the SWOT analysis conducted by BMC show that BUMDes could carry out an aggressive strategy. In addition, it also produces a new BMC Design as an improvement alternative choice strategy for customer segments, channels, revenue streams, and customer relationships that can be used for business development, especially during this COVID-19 pandemic.